SKEMA PELAYANAN KESEHATAN PRA-UPAYA SEBAGAI STRATEGI KELUAR DARI PERMASALAHAN PEMBERHENTIAN PROGRAM JARING PENGAMAN SOSIAL BIDANG KESEHATAN DI DIY (PRE-PAID HEALTH CARE SCHEME AS AN EXIT STRATEGY OF SUSPENSION OF THE HEA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Introduction: A rescue program known as Health Sector Social Safety Net Program (JPSBK) has been implemented to overcome the worse impact of crisis in Indonesia. The program has increased access and utilization of health services especially for indigent people. However, because of limited budget availability, the program will be suspended soon. The question is how an exit strategy formulation should be developed based on evidence from the field. Method: A cross-sectional study design was conducted to respondents having and non having health card. Using a simple random sampling 50% health centers in Yogyakarta province were selected. Using a circular random sampling 11 respondents having and 11 non having health cards were selected. Data on respondent characteristics, social-economic status, willingness to pay and benefit packages and other related data were collected using a structured questionnaire. Results: More than 50% of health card holders stated that they willing to pay monthly premium if the JPSBK program is suspended. About 75%, 16.5% and 8.2% of them are willing to pay monthly premium less than Rp1000, Rp1500-3000 and above Rp5000 respectively, while 15% of non-health card holders are willing to pay above Rp5000. The result showed that there is a potential for choosing a prepaid health care scheme to be an exit strategy if the JPSBK program is suspended or regional government budget is limited. The readiness of the community to participate in the pre-paid health care scheme is determined by willingness to pay and trust rather than the ability to pay. About 44% of health card holder chose health center service for their benefit package and 28% chose a comprehensive services. It showed that health card holders were sensitive to amount of premium in choosing the benefit package. When they have to pay twofold of the original premium those who choose comprehensive services dropped to be only 12%. Conclusions: The pre-paid health care scheme is potential to be an exit strategy if the JPSBK program is suspended. Majority of the community including health card holders are ready to participate in the scheme. Keywords: crisis, social safety net program, ability to pay, willingness to pay, exit strategy, pre-paid health care.